Clinical Profiles and Outcomes of Patients With Placenta Accreta Spectrum at Dr. M. Djamil Hospital, Padang During 2019 –2022 - Sriyanti, Roza; Sri Rahayu MK (Andalas Obstetrics And Gynecology Journal, 2025)
Objective: Placenta accreta spectrum (PAS) is one of the severe obstetric complications which can cause serious morbidity and mortality to both maternal and neonatal. The incidence of PAS increases globally because of the increasing rate of cesarean deliveries (CS). The aim of this study was to describe the clinical profiles and outcomes of patients with PAS during 2019-2022 at Dr. M. Djamil Hospital, Padang. Method: This study was a retrospective descriptive study that had women with PAS who gave birth and referred to Dr. M. Djamil Hospital Padang, from January 2019-December 2022 as study participants. This study described clinical profiles, PAI score and USG findings and maternal neonatal outcomes of patients with PAS. Result: One hundred eighty-seven cases were involved in this study. Most women with PAS aged ≥ 35 years (45%), parity 2 (47%), previous CS (96%), ≥ 2 times CS history (59%). A PAI score ≥ 5 has the higher proportion (66%) than a PAI score <5. There were still 53 patients (28%) who were admitted in intrapartum and postpartum. Most of the participants underwent hysterectomy (74%). Conclusion: Advanced maternal age, multiparity, previous CS, and placenta previa were risk factors for PAS. PAI score, which combines previous CH hostory and USG findings in antenatal care, can assist in determining whether pregnant women have a high risk of PAS. Antenatal diagnosis and proper perioperative management in PAS are needed to optimize maternal and neonatal outcomes.  Keywords: Placenta accreta spectrum, clinical profiles, Outcomes